2005
DOI: 10.1158/1078-0432.ccr-04-2597
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Evidence for the Independent Origin of Multifocal Papillary Tumors in Patients with Papillary Renal Cell Carcinomas

Abstract: Purpose: In patients with papillary renal cell carcinoma, it is not uncommon to find two or more anatomically distinct and histologically similar tumors at radical nephrectomy.Whether these multiple papillary lesions result from intrarenal metastasis or arise independently is unknown. Previous studies have shown that multifocal clear cell renal cell carcinomas express identical allelic loss and shift patterns in the different tumors within the same kidney, consistent with a clonal origin. However, similar clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 53 publications
1
83
0
1
Order By: Relevance
“…Microarray analysis of 120 gastric tumors revealed that caspase-2 was only expressed in 35% of tumor samples despite high expression in normal gastric tissue. 31 Downregulation of caspase-2 expression has been reported in renal cell carcinoma, 32,33 and missense mutations in CASP2 have been described in lung and ovarian tumors. 34 The promoter region of CASP2 contains a CpG island 35 and may be subject to methylation-mediated epigenetic silencing in lung adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray analysis of 120 gastric tumors revealed that caspase-2 was only expressed in 35% of tumor samples despite high expression in normal gastric tissue. 31 Downregulation of caspase-2 expression has been reported in renal cell carcinoma, 32,33 and missense mutations in CASP2 have been described in lung and ovarian tumors. 34 The promoter region of CASP2 contains a CpG island 35 and may be subject to methylation-mediated epigenetic silencing in lung adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Positivity Fluorescence in situ hybridization (FISH) analyses were performed as described previously. [13][14][15][16][17][18] Briefly, multiple 4-μm sections were obtained from formalin-fixed paraffin-embedded tissue blocks containing neoplastic tissue. A hematoxylin and eosinstained slide from each block was examined to identify areas of neoplastic tissue for FISH analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The method of analysis has been partially described previously. [13][14][15][16][17][18] In brief, for each slide, 100-150 nuclei from tumor tissue were …”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence In Situ Hybridization Analysis FISH was performed as described previously [10][11][12][13][14][15][16][17] with centromeric a-satellite DNA probes for chromosome 1 (centromeric enumeration probe (CEP) 1, spectrum orange), chromosome 2 (CEP 2, spectrum orange), chromosome 6 (CEP 6, spectrum green), chromosome 10 (CEP 10, spectrum green), and chromosome 17 (CEP 17, spectrum orange) (Figure 2). All the probes were from Vysis (Vysis, Downers Grove, IL, USA).…”
Section: Tissue Samplesmentioning
confidence: 99%